Soledad S. Reyes and the quest/ions of Philippine kritika - Caridad, Carmencita E. (Animo Repository, 2016)
This study examines the critical views of Reyes on Tagalog literature, womens literature and popular culture. It seeks to be a complement to Salungat: A Soledad S. Reyes Reader which foregrounds the framework of Reyes critical oeuvre. Moreover, this present study is a quest of how the critical works of Reyes her own questions and continued quests in Philippine kritika- are a response to our othering ourselves. It navigates with the "critical imperative" of Isagani Cruz; that is, in light of our condition and situation of "the other Other," Filipino critics are addressed the crucial task of inscribing and re-inscribing a Philippine kritika, guided by the dynamic re-turn to critical tradition, and his proposed three parameters that should be observed in the formation of what he calls makabayan at malayang kritika: the rejection of expressive realism, the abandonment of Western Formalism, and the refusal of the patriarchal structures of Western Criticism. While the study argues that Reyes as a critic responds to our othering ourselves in the field of Philippine literature and kritika, it also re-considers Reyes own theoretical positions and critical arguments vis-à-vis her specific critical views expressed in her critical essays on Tagalog literature, womens literature and popular culture.